On the preparation and antibacterial activity of emulsions stabilized with nanocellulose particles. (December 2016) - Mikulcová, Veronika; Bordes, Romain; Kašpárková, Věra
Abstract: Formation, droplet size and antibacterial activity of emulsions stabilized with cellulose particles, namely cellulose nanocrystals (CNCs) and microfibrillated cellulose (MFC) were investigated. The effects of the oil-in-water ratio (10/90 to 40/60), type and concentration of cellulose (0.1–1.0%) on the physico-chemical characteristics of the emulsions containing three different antimicrobial oils (cinnamaldehyde, eugenol and limonene) were studied. Emulsions were characterized in terms of emulsification indexes, encapsulation efficiency and droplet size and distribution. Stability during the eight-week storage period and after mild centrifugation were evaluated. The results showed that it is possible to produce oil-in-water CNC and MFC-stabilized Pickering emulsions with antimicrobial oil content as high as 40 wt%. Furthermore, emulsions showed good stability during storage and towards mild centrifugation. Antibacterial activity of the emulsions investigated using agar diffusion and broth dilution methods was mainly influenced by the type and content of antibacterial oil. Type of nanocellulose particles used for stabilization of emulsion droplets showed only a minor contribution, when high concentrations of oil were used. Results also suggested that the antibacterial effect was dependent primarily on direct interaction between emulsion droplets and pathogens, while the impact of free, non-encapsulated oil was only marginal. However, when low concentrations of emulsion were used, the role of the nature of nanocellulose could be evidenced, and MFC-stabilized emulsions exhibited better antibacterial activities compared to CNC-stabilized. Graphical abstract: Highlights: Nanocellulose-based Pickering emulsions with essential oils show antibacterial properties. Up to 40 wt% oil can be emulsified with more than 95% encapsulation efficiency. At low concentration, nanocellulose type influences the antibacterial activity and MFC-stabilized systems performs better. Overall antibacterial activity is controlled mainly by the oil encapsulated in the droplets.